2019
DOI: 10.1111/pedi.12881
|View full text |Cite
|
Sign up to set email alerts
|

Partial remission in type 1 diabetes and associated factors: Analysis based on the insulin dose‐adjusted hemoglobin A1c in children and adolescents from a regional diabetes center, Auckland, New Zealand

Abstract: Background Partial remission (PREM) by the insulin dose‐adjusted HbA1c (IDAA1c) method has not been evaluated for the combined associations of ethnicity and socioeconomic status in children and adolescents with type 1 diabetes (T1D). Objective To investigate prevalence and predictors of PREM defined by IDAA1c. Methods Six hundred fourteen of 678 children (aged <15 years) with new‐onset T1D (2000‐2013) from a regional pediatric diabetes service (Auckland, New Zealand). Results Overall rate of PREM at 3 months w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
11
0
3
Order By: Relevance
“…In Poland, PCR prevalence was estimated in 61.8% of 186 patients newly diagnosed with T1D and followed-up over 24 months and in 59% of 194 children with at least 4 years of T1D duration [ 2 , 29 ]. Chiavaroli et al reported an overall rate of partial remission at 3 months of 42.4% in a cohort study of 678 New Zealand patients aged <15 years [ 30 ]. A report from Sweden described a rate of 80% of remitters among 149 children and adolescents (0–16 years) with new-onset of T1D [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, PCR prevalence was estimated in 61.8% of 186 patients newly diagnosed with T1D and followed-up over 24 months and in 59% of 194 children with at least 4 years of T1D duration [ 2 , 29 ]. Chiavaroli et al reported an overall rate of partial remission at 3 months of 42.4% in a cohort study of 678 New Zealand patients aged <15 years [ 30 ]. A report from Sweden described a rate of 80% of remitters among 149 children and adolescents (0–16 years) with new-onset of T1D [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…And timely PR diagnosis facilitates adjustments of the therapy, so as to prevent acute events during the first year of T1D (19). Though PR only lasts for no more than a year, the occurrence of PR can also help with the prediction of long-term diabetes complications in T1D patients (3)(4)(5)20).…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of this disease, some of the newly diagnosed patients might experience a special period termed as the partial remission (PR) phase, which is characterized by satisfactory glycemic control with reduced daily insulin requirements and the transient restoration of b cell function (2). The improved glycemic control during the PR calls for an adjustment of the insulin regiment in order to avoid acute events, and the presence of PR phase is associated with a lower risk of developing chronic complications (3)(4)(5). Therefore, it is of great clinical and research significance to guarantee the diagnostic accuracy of PR.…”
Section: Introductionmentioning
confidence: 99%
“…New parameters are needed to define the PRP or preserved beta-cell reserve period. Although several studies [11][12][13] focused on the PRP and investigated PRPrelated factors, data related to the glycemic parameters during the PRP are limited. Meng et al examined the relationship between blood glucose fluctuations during various phases of diabetes and oxidative stress and showed that the mean glucose, glucose SD, the mean amplitude of glycemic excursions (MAGE) and incremental area under the blood glucose curve (IAUC) levels during the PRP were lower than those during the acute metabolic disturbance and long-standing phases [14].…”
Section: Discussionmentioning
confidence: 99%